A review: Analysis and development of heat–mass synergy theory. (November 2022) - Qu, Min; Zhang, Yongliang; Zhang, Xilong; Jia, Yuyue; Fu, Cuicui; Yao, Qi; Cao, Jianxia
Abstract: In this work, a review of the theory and application of heat and mass synergy is carried out. Since the field synergy theory was proposed, it has not only been greatly developed in the field of heat transfer but also has been explored and studied in the field of mass transfer and heat and mass synergy. In order to clarify the development and improvement process of field synergy theory and sort out its application and development trend, this paper conducts theoretical research on the proposal and controversy of field synergy theory and the derivation of the field synergy formula under different conditions. The field synergy equations based on different fluid states such as laminar flow and turbulent flow in the case of heat transfer, mass transfer, and heat–mass synergy are summarized. Optimizing the synergy application of heat–mass in engineering practice can significantly improve its heat and mass transfer capabilities. Although the field synergy principle has certain advantages in enhancing mass and heat transfer, it cannot take into account the power consumption in practical engineering applications. Therefore, combining the principle of field synergy with other theories to improve the comprehensive performance of heat and mass transfer has provided a way of thinking for future research. Highlights: The development and controversy of pair-field synergy theory were discussed. The field synergy equations under different conditions were summarized. The research progress of heat–mass​ synergy theory was analyzed. Combined with other theories to strengthen the heat and mass transfer is considered.